Scampoli di ricerche critiche su Petrarca e la sua fortuna - Cherchi, Paolo (Studi filologici e letterari, 2023)
Rather, the "scraps" collected in this volume are "fragments" understood in the Petrarchan sense, as flakes of an organic whole, as moments that give a sense of what time is. Petrarch is an accessible author because he is flat and elegant, but he is actually scholarly without being ostentatious about it, so it is surprising every time one discovers a web of literary allusions behind dimly presented data. Each "remnant" bears witness to these occasional discoveries, to readings that seek not allegorical "supersense" but the scholarly undercurrent of this writing. An early section points to the "solitary life" as the matrix of this familiarity and intimacy with ancient texts. Another and more extensive section identifies specific "sources" on points where one would not suspect their presence. Another group concerns Petrarch's fortunes, that is, the different readings of his work given in different environments and eras. Finally, an essay on the "private" world of the author, who fights against superstitions but does not feel completely freed from them. Thus not an "organic" book in the traditional sense, and yet a unified work in that it is devoted to the reconstruction of a style of work and the various ways of enjoying it.